2018
DOI: 10.1186/s13046-018-1002-1
|View full text |Cite
|
Sign up to set email alerts
|

Classification of triple-negative breast cancers based on Immunogenomic profiling

Abstract: BackgroundAbundant evidence shows that triple-negative breast cancer (TNBC) is heterogeneous, and many efforts have been devoted to identifying TNBC subtypes on the basis of genomic profiling. However, few studies have explored the classification of TNBC specifically based on immune signatures that may facilitate the optimal stratification of TNBC patients responsive to immunotherapy.MethodsUsing four publicly available TNBC genomics datasets, we classified TNBC on the basis of the immunogenomic profiling of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
313
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(354 citation statements)
references
References 55 publications
16
313
2
Order By: Relevance
“…Mounting evidence has identified that the immune cell dysfunction within the HNSC-TME promotes immunosuppression and so the associated tumor survival and progression, which later demands therapeutic intervention to counteract this process [35,36]. In this study, we analyzed the immune cell infiltration in a meta-cohort of 1029 HNSC samples and categorized the HNSC into three distinct immune subtypes.Our analysis indicated that density of CD4 + T cells, CD8 + T cells, plasma cells, and M1 Macrophages cells along with the higher immune score were correlated to the patient's prognosis, which is in line with the previous studies [37,38]. This emphasizes the fact that the pre-existing immune response has an anti-tumor effect and positively affects the response to immunotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Mounting evidence has identified that the immune cell dysfunction within the HNSC-TME promotes immunosuppression and so the associated tumor survival and progression, which later demands therapeutic intervention to counteract this process [35,36]. In this study, we analyzed the immune cell infiltration in a meta-cohort of 1029 HNSC samples and categorized the HNSC into three distinct immune subtypes.Our analysis indicated that density of CD4 + T cells, CD8 + T cells, plasma cells, and M1 Macrophages cells along with the higher immune score were correlated to the patient's prognosis, which is in line with the previous studies [37,38]. This emphasizes the fact that the pre-existing immune response has an anti-tumor effect and positively affects the response to immunotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have reported a correlation between programmed death-1/ligand-1 (PD-1/PD-L1) and immune activity in tumors in triple-negative breast cancer [20]; Moreover, a large number of studies have shown that ssGSEA and ESTIMATE are highly reliable in the evaluation of tumor immune strati cation and immune invasion analysis [22,[49][50][51][52]. Furthermore, we analyzed the correlation between the expression of GNG5 and in ltration level of tumor-in ltrating immune cells using TIMER.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting enriched pathways were analyzed based on nominal (NOM) P-values and normalized enrichment scores (NES). We examined the relationship between the expression of GNG5 in glioma tissues and the immune microenvironment using the single-sample gene set enrichment analysis (ssGSEA) to calculate the enrichment of 29 immune cell geneset signatures in each glioma sample based on data downloaded from the CGGA database [19][20][21].…”
Section: Gene Set Enrichment Analysis (Gsea) and S Immune Correlationmentioning
confidence: 99%
“…To understand the overall situation of immune in ltration and facilitate visualization, we corrected the data as follows. For each ssGSEA score, Xi was replaced with Xi ′ with the equation Xi ′ = (Xi − Xmin)/(Xmax − Xmin), where Xmin and Xmax represent the minimum and maximum values of the ssGSEA score in the THCA sample, respectively [17]. The same method was also applied to the other nine GEO datasets.…”
Section: Single-sample Gene Set Enrichment Analysis (Ssgsea)mentioning
confidence: 99%